Orchestrating Multi-Cloud Environments for Enhanced Flexibility and Resilience - Voruganti, Kiran Kumar (Journal of Technology and Systems, 2024)
Purpose: This paper examines the essential role of multi-cloud orchestration in navigating the complexities of the contemporary cloud computing landscape, aimed at optimizing the deployment and management of cloud resources across diverse environments. Methodology: Utilizing a systematic review of scholarly articles, industry reports, and case studies, including the Flexera 2021 State of the Cloud Report and insights from Gartner, alongside academic contributions from researchers like Jamshidi et al. and Garg et al., this study delves into the strategies and tools facilitating effective multi-cloud orchestration. Findings: The research highlights multi-cloud orchestration as a critical enabler for enhancing operational efficiency, resilience, and cost-effectiveness in cloud deployments. It emphasizes the strategic benefits of orchestrating a heterogeneous mix of cloud services, including public, private, and hybrid clouds, to meet the intricate demands of modern applications. The study underscores the importance of advanced orchestration tools in ensuring seamless operations, security, and compliance across multi-cloud architectures. Unique contributor to theory, policy and practice: By following the principles outlined in this paper, organizations can leverage multi-cloud orchestration to unlock the full potential of their cloud investments and achieve a well-orchestrated symphony of success.